Anticancer properties and prevention of metabolic syndrome by probiotic-enriched powdered human milk - Valerie Robichaud; Shiv Shankar; Augusto Tasch Holkem; Stephane Salmieri; Blanca R. Aguilar-Uscanga; Mathieu Millette; Monique Lacroix (Food Bioscience, 2024)

Screening and Characterization of Some Lactobacillaceae for Detection of Cholesterol-Lowering Activities - Martin Frappier; Julie Auclair; Samir Bouasker; Sathursha Gunaratnam; Carine Diarra; Mathieu Millette (Probiotics and Antimicrobial Proteins, 2022)
Dyslipidemia, specifically abnormal levels of low-density lipoprotein cholesterol (LDL-C), is an important risk factor of cardiovascular disease. Evidence showing the promising abilities of probiotics to lower total cholesterol or LDL-C has, however, not yet convinced experts to recommend probiotic bacteria as treatment for blood lipid management. Therefore, there are opportunities for the development of new efficient cholesterol-lowering probiotics. Bile salt hydrolase (BSH) and feruloyl esterase (FAE) are bacterial enzymes proposed to explain the cholesterol-lowering capacity of some bacteria and have both been shown to be responsible for lipid reduction in vivo. Here, in order to select for cholesterol-lowering bacteria, 70 strains related to Lactobacillaceae were screened for BSH and FAE activities. Based on this two-way screening approach, two bacteria were selected and assessed for their capacity to assimilate cholesterol in vitro, another suggested mechanism. Lactobacillus acidophilus CL1285 showed BSH and FAE activity as well as capacity to assimilate cholesterol in vitro. Lactiplantibacillus plantarum CHOL-200 exhibited BSH activity and ability to assimilate cholesterol. These properties observed in vitro make both strains good probiotic candidates for the management of dyslipidemia. Further investigation is needed to assess their ability to reduce blood cholesterol in human trial.

The Acid-Dependent and Independent Effects of Lactobacillus acidophilus CL1285, Lacticaseibacillus casei LBC80R, and Lacticaseibacillus rhamnosus CLR2 on Clostridioides difficile R20291 - Sathursha Gunaratnam; Carine Diarra; Patrick D. Paquette; Noam Ship; Mathieu Millette; Monique Lacroix (Probiotics and Antimicrobial Proteins, 2021)

Importance of Molecular Methods to Determine Whether a Probiotic is the Source of Lactobacillus Bacteremia - Alla Aroutcheva; Julie Auclair; Martin Frappier; Mathieu Millette; Karen Lolans; Danielle de Montigny; Serge Carrière; Stephen Sokalski; William E. Trick; Robert A. Weinstein (Probiotics and Antimicrobial Proteins, 2016)

Influence of Environmental Factors on Bacteriocin Production by Human Isolates of Lactococcus lactis MM19 and Pediococcus acidilactici MM33 - Mélanie Turgis; Khanh Dang Vu; Mathieu Millette; Claude Dupont; Monique Lacroix (Probiotics and Antimicrobial Proteins, 2016)